Gambaran nilai laktat, ScvO2, dan PvaCO2 GAP pada pasien sepsis di Rumah Sakit Umum Haji Adam Malik Medan - Muhammad Arif Siregar; Achsanuddin Hanafie; Rr Sinta Irina (Jurnal SAGO Gizi dan Kesehatan, 2024)
Background: We need a prognostic predictive value in sepsis and septic shock patients to determine the aggressiveness of the therapy we will choose. We use various methods to predict patient mortality. To assess tissue perfusion disorders, we need markers. Lactate, SvO2, and PvaCO2 gaps are commonly used as early biomarkers to assess tissue perfusion and cellular oxygenation.Objectives: To describe the value of lactate, ScvO2, and PvaCO2 gap in septic patients.Methods: This study is an analytical descriptive study that examines the lactate value, ScvO2, and PvaCO2 gap in 40 patients diagnosed with sepsis. We conducted the study in the emergency room (IGD) of the Hajj Adam Malik Hospital in MedanWe began by gathering information from research samples that satisfied the inclusion and exclusion criteria, providing explanations to the families of patients involved in the study, obtaining blood samples, and conducting data analysis. We used ultranonography to collect blood from the central vein. The SPSS application carried out data analysis using univariate tests.Results: In this study, the lactate values were found in the normal range with an average of 1.45 ± 1.81, the ScvO2 value increased by an average of 91.29 ± 7.91, and the PvaCO2 gap value increased by an average of 11.52 ± 8.28.Conclusion: In this study, lactate values were above normal, with AGDA parameters indicating metabolic acidosis expression. ScvO2 PvaCO2 gap value that increased.